Estudio de factibilidad para la creación de una empresa inmobiliaria virtual en la ciudad de Pereira Risaralda (2012)
Given the current importance of the problem of homelessness at the national and international level and the fragility that this has in a world where the practices of a globalized market prevail and there is no housing understanding that eradicates the lack of these goods. With the present proposal of business of the feasibility study of the real estate agent SAIM (active real estate virtual service) that will work in the city of Pereira Risaralda, it is looked for to create a new alternative of doing business, being the first interactive Web page, where all the clients can access an electronic address and this will take them to a virtual and important world related to issues of purchase and sale of housing. In this way it is sought to make available to the people a website, where on entering they can know, through the specialized site, and at the same time solve the doubts they have about the purchase and sale of real estate in a virtual way, entering the website www.saim-inmobiliaria.tk We also want to provide the call center service for those people who do not like or who are not technology, who prefer a personalized treatment, the service that will be provided through this page will be 24 hours a day, 7 days of the week without interruptions and with an immediate response time since being interactive will have virtual advisors that make the complete accessory in any place, time or country where the client is